NEW SKELETON-LESS HOMOSCLEROMORPHS (PORIFERA, HOMOSCLEROMORPHA) FROM THE CARIBBEAN SEA: EXCEPTIONS TO RULES ARE DEFINITELY COMMON IN SPONGE TAXONOMY - Ruiz, Cesar; Ereskovsky, Alexander; Perez, Thierry (Zootaxa, 2022)
Currently composed of only one order and two families, the class Homoscleromorpha has undergone significant changes in its systematics over the past 20 years. We combined morphological, cytological and molecular (CO1) data to describe three new aspiculate Homoscleromorpha, two Plakinidae and one Oscarellidae. These three sponges live in the dark submarine caves of the Lesser Antilles (Caribbean Sea). Aspiculortis gen. nov. is part of a clade including spiculate Plakortis species. Aspiculortis garifuna gen. nov. sp. nov. is characterized by an original pseudo criblate smooth surface, with a network of translucent canals ending in prominent oscula, and by one type of vacuolar cell concentrated in the ectosome. Aspiculophora papillata sp. nov. is characterized by a papillate surface, a morphological trait that is recorded for the first time among Homoscleromorpha, and one abundant type of vacuolar cell randomly distributed in the mesohyl. Oscarella minka sp. nov. is characterized by a smooth surface and two types of vacuolar cells, one principally found in the ectosome, and a second type which is randomly distributed and which harbors original inclusions. These three new Homoscleromorpha present an abundant microbial community in their mesohyl. After this work, the skeleton-less representatives of this sponge class include four species of Plakinidae belonging to three different genera, and all Oscarellidae described so far. The putative absence of skeleton underlines the need of more cytological descriptions of Plakinidae representatives.